Negative thermal expansion of cold-rolled Ti-Nb over a wide temperature range - Lai, Daniel Kuok Zheng (2025)
Anisotropic negative thermal expansion (NTE) of martensitic β-isomorphous Ti-alloys has been discovered to be one of the largest in magnitude among other NTE materials. Exhibition of macroscale NTE was shown to be achievable through texturing, but studies reporting on this behaviour have been conservative and have only reported within the purely martensitic region. Studies have not yet revealed the effects of phase transformation and thermomechanical property changes on the textured material when heated above the martensitic region. This work aims to study the NTE thermal stability, phase transformation sequence, and resulting mechanical properties of a cold-rolled Ti-22Nb (at.%) elevated to temperatures outside the purely martensitic region. The evolution of macroscale thermal expansion of cold-rolled Ti-22Nb was uncovered by thermal cycling to 150, 250, 350, 450, 550 °C. The magnitude of contraction along the rolling direction increased with temperature until a maximum contraction was achieved at 320 °C. Expansion was observed beyond that temperature and the specimen retained NTE at 150-250 °C, zero thermal expansion at 350 °C, and positive thermal expansion at 450-550 °C. Long-term NTE thermal stability of cold-rolled Ti22Nb was investigated through isothermally aging the specimen at 150, 250 °C for 10, 100, 1000 hours. In both cases, the NTE of the sample decreased with duration. Diffusional rejection of Nb was behind the minimal loss of NTE after 1000h at 150 °C, while zero thermal expansion was achieved after 1000h at 250 °C. An unusual destruction and precipitation of ω phase was detected while aging at 150 °C. The phase transformations leading to the deterioration of NTE when heating to 350-550 °C was studied and sequenced according to the occurring temperatures. The non-linear nature of macroscale NTE was reasoned to stem from direct translation of the lattice NTE. Diffusional rejection of Nb was the main mechanism leading to loss of NTE and eventually leading to a duplex α+β microstructure. An unusual occurrence of the same diffusion occurring at staggered temperatures was observed was reasoned to be due to the cold-work nature of the specimen.